Efficient Allocation of Labor Maximizes Brood Development and Explains Why Intermediate-Sized Groups Perform Best During Colony-Founding in the Ant, Pogonomyrmex californicus - Shaffer, Zachary J.; Dreyer, Sara; Clark, Rebecca M.; Pratt, Stephen C.; Fewell, Jennifer H. (Frontiers in Ecology and Evolution, 2022)
Cooperation in nature is usually between relatives, but unrelated individuals can also cooperate, requiring significant benefits to outweigh the costs of helping non-kin. Unrelated queens of the ant, Pogonomyrmex californicus, work together to found a new colony, a phenomenon known as pleometrosis. While previous studies have shown that pleometrosis improves queen survival and worker production, little is known of the behavioral interactions within nests that explain these advantages. We aimed to determine how the optimal group size for a small, simple social group is related to group productivity and the organization of work. Collecting queens from a known pleometrotic population, we established nests with either one, three, six, or nine foundresses and observed the resulting nascent colonies for 50 days. We found that queens in social founding groups survived longer and had higher productivity. While all social groups were equally successful in producing workers, intermediate-sized groups were most successful in terms of per capita production. Inactivity increased with group size. In addition, the proportion of essential colony growth tasks performed (such as foraging and brood care) was lowest in both solitary-founded groups and in groups of nine queens. As a result, intermediate sized groups outperformed both solitary queens and groups of nine in the efficiency with which they converted eggs into workers. These results emphasize the benefits of cooperation and the ways in which group size can influence fitness and the allocation of labor in social groups.